Karakteristik, model, strategi dan keberhasilan kepemimpinan pendidikan dalam meningkatkan mutu sekolah: Studi kasus SMA Negeri 1 Banyuasin III - yani, indra (Maliki Interdisciplinary Journal, 2026)
This article discusses educational leadership, including its definition, characteristics or models, strategies, and the success of educational leadership based on the leadership at SMAN 1 Banyuasin III. Educational leadership itself is the most important pillar, especially within the scope of education. Educational leadership is an effort to invite, encourage, coordinate, or direct someone in implementing and developing education to achieve the desired goals (Puji Khamdani, 2014), by providing motivation and balancing the individual goals of the implementers. with the library research method aimed at collecting various data, such as scientific articles, journals, and books relevant to the discussionA leader is chosen with the aim of influencing an individual or a group to achieve something that has been set as a goal. The discussion results indicate that effective principal leadership is characterized by managerial skills, strong communication skills, and the active involvement of all school members in every program implemented. Participatory and adaptive leadership has been shown to improve the performance of educators and create a conducive learning environment. Therefore, quality educational leadership is a key factor in driving improvements in educational quality and achieving institutional goals on a sustainable basis.